Gender Equality In Laity Leadership Within Religious And Organizational Life At Catholic Church Of Maria Ratu Damai Walian Parish, Tomohon (A Civic Education Perspective) - Fransiska Laatung; Theodorus Pangalila; Julien Biringan (Academy of Education Journal, 2026)
This research is motivated by the evident gender distribution inequality in strategic positions among the laity, particularly in the position of field coordinator within the Parish Pastoral Council (DPP) of Maria Ratu Damai Tomohon, As well as the existence of cultural barriers and misinterpretations of teachings that limit the role of women. The purpose of this study is to obtain a comprehensive understanding of gender equality in women’s leadership, to identify the factors hindering their involvement in the DPP structure, as well as to analyze the phenomenon through the perspective of Pancasila values and Civic Education. The research method used is a qualitative approach employing the Miles and Huberman data analysis model to ensure the depth of observation. The findings of the study show that over the past 39 years: 1. Strategic leadership has been dominated by men, creating a “glass ceiling” phenomenon due to women’s low self-confidence. 2. The double burden of domestic responsibilities; 3. As well as a patriarchal culture that is not yet aligned with the implementation of the fifth principle of Pancasila. This study recommends that Church leaders implement affirmative policies, such as quotas for women’s representation, organizing leadership training programs (public speaking), and strengthening gender literacy so that the parish can become an inclusive democratic forum for all parishioners.